2021
DOI: 10.3389/fonc.2021.737399
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for Cutaneous Melanoma by Clinical and Pathological Profile: A Population-Based Study

Abstract: IntroductionAmong white people, the incidence of cutaneous malignant melanoma (CMM) has been increasing steadily for several decades. Meanwhile, there has also been a significant improvement in 5-year survival among patients with melanoma. This population-based cohort study investigates the five-year melanoma-specific survival (MSS) for all melanoma cases recorded in 2015 in the Veneto Tumor Registry (North-Est Italian Region), taking both demographic and clinical-pathological variables into consideration.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Previous studies reported an inverse association between vitamin D levels and number of mitoses [ 32 – 35 ], which may contribute to explain the higher number of mitoses in PFAS-exposed cohort in our study. In our series, mitotic index was strongly associated with patient survival as reported by many other investigators [ 36 38 ]. However, our data did not suggest an association between PFAS exposure and patient survival.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies reported an inverse association between vitamin D levels and number of mitoses [ 32 – 35 ], which may contribute to explain the higher number of mitoses in PFAS-exposed cohort in our study. In our series, mitotic index was strongly associated with patient survival as reported by many other investigators [ 36 38 ]. However, our data did not suggest an association between PFAS exposure and patient survival.…”
Section: Discussionsupporting
confidence: 88%
“…In their study, univariate analysis showed significant differences in survival between the subtypes; however in multivariate analysis with adjusted hazard ratios, they found no significant correlation between histological type and survival. Similarly, the study conducted by Buja et al, 51 identified significant differences in fiveyear survival rates among the different histological subtypes, with the nodular subtype exhibiting the poorest prognosis.…”
Section: Discussionmentioning
confidence: 68%
“…Depending on the AJCC Stage, the prognosis of the patients varies considerably. For example, 5‐year survival in stage I is 99.4%, while in stage IV it drops to 23% (Buja et al, 2021).…”
Section: Introductionmentioning
confidence: 99%